DOMINASI KLEN MASYARAKAT KAILI DALAM PARTISIPASI POLITIK PEREMPUAN PADA PARTAI POLITIK - Nisbah Nisbah (Indonesian Journal of Dialectics, 2012)
The Phenomenon of political strengthening of the local clans rely on the genealogic relationship including women’s political participation. Mastery of strategic positions in political parties representing the power of the dominant clans. Political participation of women in political parties suggests that the presence of kinship linkages with key figurs in the dominant clans. The research question is how the domination of clan in Kaili Society articulated  in political Parties. This research has been carried out by using a qualitative approach.The result of research shows that the authority of traditional institusions remain because of a determinant factor in strengthening the dominance of clan social structure. It is formed by a process of social change on traditional power system on the pust turns into the existence of such cultural institutions today, so that the dominant clan members occupy the top social status and strategic role. The central figure that take a lead in Kaili is the madika. It is increase the recruitment of female in the number but a role uin the activities of political parties precisely reduced and  weakened.